2018
DOI: 10.3390/su10020467
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Land-Use and Climate Change on Ecosystem Service in Eastern Tibetan Plateau, China

Abstract: Past years have witnessed the transformation of land use at a high frequency and a warmer and drier climate in the Eastern Tibetan Plateau region. To fully understand the spatial-temporal variation of ecosystem services against the changing global backdrop and to provide scientific ecosystem management measures for decision-making, a study was conducted to investigate the major ecosystem services: water yield, soil conservation and crop production from 1990 to 2015 in the Eastern Tibetan Plateau region. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 57 publications
(68 reference statements)
1
14
0
Order By: Relevance
“…Some studies have shown that climate change was important factor affecting ESV [28][29][30]. The above researches can draw preliminary qualitative or quantitative conclusions that meteorological factors have influence on ESV.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have shown that climate change was important factor affecting ESV [28][29][30]. The above researches can draw preliminary qualitative or quantitative conclusions that meteorological factors have influence on ESV.…”
Section: Discussionmentioning
confidence: 95%
“…This study also reveals the scattered pixels with negative NDVI trend (mostly distributed along the Yalunzangbu river), implying the ecological effects of land cover change, grassland degradation, urbanization, deforestation and desertification (Cui andGraf 2009, Shen et al 2012). Therefore, the ecological service might have reduced in eastern region (Tang et al 2018), despite the regional climate warming and wetting over the past decades.…”
Section: Characteristics Of Climate Change and Vegetation Growthmentioning
confidence: 99%
“…In addition, the changes in the two nutrient services were opposite in the land use alone and combined conditions, which suggested that distinct differentiations existed in the mechanisms that altered the nitrogen and phosphorus services under these conditions. The change of land use type, patterns, and intensity affects ESs supply through the corresponding ecological processes changes [4]. Previous studies have indicated that cultivated land has a primary positive impact on nitrogen loading while construction land mainly causes the increase of phosphorus loading [49,88].…”
Section: The Combined Effects Of Multiple Driving Forces On Ecosystemmentioning
confidence: 99%
“…For the WS and SR services, the effects of climate change alone and the combined impacts in the future (Tables 3 and 4) were more remarkable than the effects of land use alone ( Table 2), indicating that climate change is the primary driver of the changes in these services. Climate change influences the hydrological process and moisture-energy distribution directly or indirectly [4], resulting in the two services changes. In terms of temporal variation, SR change was similar to the precipitation change trend.…”
Section: The Combined Effects Of Multiple Driving Forces On Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation